Placental oxidative status in rural residents environmentally exposed to organophosphates - Chiapella, Graciela (2014)
The impact of environmental organophosphate pesticide exposure on the placenta oxidative status was assessed. Placental samples were collected from women residing in an agricultural area during pesticide pulverization period, non-pulverization period and from control group. Carboxylesterase activity was significantly decreased in pulverization period group. Enzymatic and non-enzymatic defense system, the oxidative stress biomarkers and the nuclear factor erythroid 2-related factor levels showed no differences among groups. However, in the pulverization period group, an inverse association between catalase activity and placental index, a useful metric for estimating placental inefficiency, was found. This result suggests that catalase may serve as a potential placental biomarker of susceptibility to pesticides. Further studies designed from a gene-environment perspective are needed.